СТРУКТУРА ГОТОВНОСТІ МАЙБУТНІХ УЧИТЕЛІВ ФІЗИЧНОЇ КУЛЬТУРИ ДО ФІЗКУЛЬТУРНО-СПОРТИВНОЇ ДІЯЛЬНОСТІ У ЗАГАЛЬНООСВІТНІЙШКОЛІ - Карасєвич, Сергій (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті обґрунтовано структуру готовності майбутніх учителів фізичної культури до фізкультурно-спортивної діяльності в ЗОШ, яка включає критерії: мотиваційно-ціннісний, інтелектуально-пізнавальний, діяльнісно-практичний. Мотиваційно-ціннісний критерій визначаємо як комплекс взаємозв’язаних мотивів майбутнього вчителя до роботи, що проявляється в його відносинах, інтересах в педагогічній діяльності, як сформованість цільових орієнтацій до професійної діяльності, як професійна спрямованість на занятті фізкультурно-спортивною діяльністю (мотиви, інтереси, ціннісні орієнтації, рефлексія особистісного зростання). В статье обоснована структура готовности будущих учителей физической культуры к физкультурно-спортивной деятельности в ООШ, которая включает критерии: мотивационно-ценностный, интеллектуально-познавательный, деятельно-практический. Мотивационно-ценностный критерий определяем как комплекс взаимосвязанных мотивов будущего учителя к работе, которые проявляются в его отношениях, интересах в педагогической деятельности, как сформированность целевых ориентаций в профессиональной деятельности, как профессиональная направленность на занятия физкультурно-спортивной деятельностью (мотивы, интересы, ценностные ориентации, рефлексия личностного роста). In the article the structure of readiness of future teachers of physical culture to physical culture and sports activities in school, which includes criteria: motivational-valuable, intellectual-cognitive, activity and practice. Motivational value criterion is defined as a set of interrelated motives of future teachers to work, which is evident in his relationships, interests in pedagogical activity, as the formation of target orientations to professional activities as a professional orientation in the activity sports activities (motives, interests, values, reflection, personal growth). Intellectual-cognitive criterion is characterized by the number and quality of acquired knowledge on the complex of disciplines (education, psychology, group sports, and the like), which are necessary to prepare students for sports activities. Activity and practical criterion is characterized by a system-generated pedagogical skills used by the future teacher in physical training and sport activities. Each criterion is characterized by compliance indicators.